ARTIFICIAL INTELLIGENCE IN HUMAN RESOURCE MANAGEMENT: OPPORTUNITIES AND RISKS FOR SUSTAINABLE ENTERPRISE DEVELOPMENT - SAMOLIUK, Nataliia; YURCHYK, Halyna; KROL, Vita (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the use of artificial intelligence (AI) algorithms in human resource management (HRM) and their impact on sustainable enterprise development. The focus is placed on the key areas of AI application in HRM – recruitment, workforce planning, and employee development. It is shown that algorithmic systems can automate candidate screening, increase the accuracy of workforce demand forecasting, and create personalized employee development pathways. These opportunities strengthen enterprises’ competitiveness and align with the Sustainable Development Goals (SDGs), particularly SDG 8 “Decent Work and Economic Growth” and SDG 9 “Industry, Innovation and Infrastructure”. At the same time, significant risks associated with the implementation of AI in HRM are emphasized. Among them are algorithmic bias that may reproduce social and gender inequalities, the threat of displacing certain employees due to automation of routine tasks, and the risk of reducing employee development to an overly technical approach that overlooks individual needs. The paper summarizes findings from recent international research and practical corporate cases (IBM, Microsoft), which demonstrate both the positive effects of algorithmic adoption in HR practices and the necessity of introducing responsible AI principles, including human oversight in decision-making.The results suggest that the adoption of AI in HRM can become a significant driver of sustainable enterprise development, provided that ethical aspects are considered, HR professionals’ digital competencies are enhanced, and international practices are adapted to the national context. This creates a basis for further research aimed at developing metrics of responsible AI use in HRM and assessing its impact on the social, economic, and environmental dimensions of sustainability.
Keywords: artificial intelligence; human resource management; HR digitalization; sustainable development; sustainable development goals; algorithmic bias; ethical risks